Pengaruh Model Project Based Learning (PjBL) Berbasis STEM terhadap Keterampilan Proses Sains Siswa SMP dalam Pembelajaran IPA - Fitriatul Aulia Rahma; Ulin Nuha (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to investigate the impact of the Project Based Learning (PjBL) model integrated with STEM on the Science Process Ability (PPP) of junior high school students in science subjects. The basis of this research departs from the low scientific competence of students, especially in the aspects of formulating hypotheses, compiling experiments, applying concepts, and conveying results, as reported by previous studies. This study used a quasi-experimental design with a pretest-posttest control group design involving two classes, namely an experimental class that obtained STEM-based PjBL learning, and a control class that used a scientific approach. Data collection methods include tests, observations, interviews, and documentation. Data analysis was carried out through normality tests, homogeneity tests, Mann-Whitney U tests, and N-Gain calculations. The findings of the study showed that the STEM-based PjBL model exerted a significant influence on students' science process skills which were characterized by a p-value on the Mann-Whitney U test of 0.003 (< 0.05). The increase in scientific competence was strengthened by an N-Gain value of 0.61 (medium category), with the highest increase in the aspect of compiling experiments and delivering results. The results of this study confirm that the application of STEM-based PjBL is able to create contextual, applicative, and effective learning in strengthening students' scientific mindsets.